1986
DOI: 10.1139/x86-244
|View full text |Cite
|
Sign up to set email alerts
|

Respiration in lodgepole pine parasitized by American dwarf mistletoe

Abstract: Rates of dark respiration were determined for foliated twig tips of branches from Pinuscontorta and for aerial shoots of Arceuthobiumamericanum. Tree samples were obtained from twigs of branches on uninfected trees, twigs from uninfected branches on infected trees, and from uninfected twigs of branches having localized infections. Rates of dark respiration were significantly lower for twigs from infected trees as compared with twigs from uninfected trees. The rate of dark respiration for aerial shoots of A. am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Changes in biomass allocation caused by dwarf mistletoe are likely to upset allocational balances to the detriment of hosts independently of parasitic effects. Specifically, previous studies (Tinnin and Knutson 1980;Broshot et al 1986;Wanner and Tinnin 1986) suggest that dwarf mistletoe may increase total tree leaf area to sapwood cross sectional area ratios (A L :A S ). The potential consequences of higher A L :A S ratios in infected trees include increased demand of water relative to supply, and therefore, increased susceptibility to drought stress.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Changes in biomass allocation caused by dwarf mistletoe are likely to upset allocational balances to the detriment of hosts independently of parasitic effects. Specifically, previous studies (Tinnin and Knutson 1980;Broshot et al 1986;Wanner and Tinnin 1986) suggest that dwarf mistletoe may increase total tree leaf area to sapwood cross sectional area ratios (A L :A S ). The potential consequences of higher A L :A S ratios in infected trees include increased demand of water relative to supply, and therefore, increased susceptibility to drought stress.…”
Section: Introductionmentioning
confidence: 99%
“…These parasitic plants directly divert resources from their hosts (Hull and Leonard 1964;Miller and Tocher 1975;Schulze and Ehleringer 1984;Marshall and Ehleringer 1990;Rey et al 1992;Marshall et al 1994) and may induce host physiological responses that result in abnormal growth patterns and altered resource allocation (Tinnin and Knutson 1980;Livingston et al 1984;Broshot et al 1986;Wanner and Tinnin 1986). Previous work on mistletoes has focused on the parasitic nature of the mistletoe and the relative physiological performance of mistletoes and their hosts (Fisher 1983;Glatzel 1983;Hollinger 1983;Ehleringer et al 1986;Goldstein et al 1989;Marshall and Ehleringer 1990;Rey et al 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated that transpiration rates of dwarf mistletoe shoots are higher than those of host tissues, which may increase both water stress in the host and allocation of resources to mistletoe shoots (Fisher 1983;Tocher et al 1984;Wilson and Calvin 1996). Additional evidence indicates that infection increases needle surface area while decreasing volume (Tinnin and Knutson 1980;Wanner and Tinnin 1986). Such shifts in the distribution of biomass in the host crown could lower water-use efficiency, resulting in lower tolerance to drought stress (Sala et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the significant changes in branch structure that result from the infection of P. contorta by A. americanum, it is known that the starch content of needles increases (Broshot and Tinnin 1986), respiratory rates decrease (Wanner and Tinnin 1986), and patterns of carbon allocation change (Leonard and Hull 1965). The many changes in structure and function that occur after infection are at least related to, if not part of, the mechanisms that cause host decline.…”
Section: Resultsmentioning
confidence: 99%